Validity and reliability of chronic tic disorder and obsessive-compulsive disorder diagnoses in the Swedish National Patient Register. Issue 6 (22nd June 2015) - Rück, Christian; Larsson, K Johan; Lind, Kristina; Perez-Vigil, Ana; Isomura, Kayoko; Sariaslan, Amir; Lichtenstein, Paul; Mataix-Cols, David
Abstract : Objectives: The usefulness of cases diagnosed in administrative registers for research purposes is dependent on diagnostic validity. This study aimed to investigate the validity and inter-rater reliability of recorded diagnoses of tic disorders and obsessive-compulsive disorder (OCD) in the Swedish National Patient Register (NPR). Design: Chart review of randomly selected register cases and controls. Method: 100 tic disorder cases and 100 OCD cases were randomly selected from the NPR based on codes from the International Classification of Diseases (ICD) 8th, 9th and 10th editions, together with 50 epilepsy and 50 depression control cases. The obtained psychiatric records were blindly assessed by 2 senior psychiatrists according to the criteria of the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) and ICD-10. Primary outcome measurement: Positive predictive value (PPV; cases diagnosed correctly divided by the sum of true positives and false positives). Results: Between 1969 and 2009, the NPR included 7286 tic disorder and 24 757 OCD cases. The vast majority (91.3% of tic cases and 80.1% of OCD cases) are coded with the most recent ICD version (ICD-10). For tic disorders, the PPV was high across all ICD versions (PPV=89% in ICD-8, 86% in ICD-9 and 97% in ICD-10). For OCD, only ICD-10 codes had high validity (PPV=91–96%). None of the epilepsy or depression control cases were wrongly diagnosed as having tic disorders or OCD, respectively. Inter-rater reliability was outstanding for both tic disorders (κ=1) and OCD (κ=0.98). Conclusions: The validity and reliability of ICD codes for tic disorders and OCD in the Swedish NPR is generally high. We propose simple algorithms to further increase the confidence in the validity of these codes for epidemiological research.